(3QSGdI aj GdcGahQs - (3CHh Ydj CMeO Hf YHO GdQMef , GHf efOhjg GdCUagGfjs
(3ChdgG (B:s
(3bGd CHhYdj dMb eGbjd dh ScJ ef dGjYde, jSbW GdENJdGa , hPdc Cf GdENJdGa aj GdTF EfeG ef Jcde GdLgd ajg HeG dGjYdeg s
(3BNQgG (B:s
(3agPG eG MVQfj ef Gdbhd aj GdcGahQ hCfcQ Cf jchf ajg eYJQV , hdG CLMO efg eGjfJgi Ydi ehVY GdNdd ajg hGddg hdi GdJhajb s
(3GfXQgG eY GdeQTO Qbe (B"730"s
(3fSNI KGfjI ecQQI Yf GdSGHbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B111 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj edj (B(1568) s
Keywords: (3GdWHs